Hydronephrosis in a Bitch with Ovarian Remnant Syndrome - Postsurgical Complications - Machado Lima, Geyse Maria; Alves da Silva, Ana Caroline; Bueno Borges, Luisa Pucci; Nascimento de Carvalho, Ana Estelita; Monteiro, Francisco Décio Oliveira; Souza Domingues, Sheyla Farhayldes; Franchi João, Carolina; Maia Teixeira, Pedro Paulo (Acta Scientiae Veterinariae, 2022)
Background: Elective ovariohysterectomy (OH) is minimally invasive, but when performed incorrectly, it can lead to postsurgical complications, such as stump pyometra, ovarian remnant syndrome and foci of adhesion generated by tissue reactions to threads and materials used in vessel hemostasis. The formation of adhesions and successive surgeries predisposes patients to other diseases, such as ureteral obstruction and hydronephrosis. Thus, we reported a case of hydronephrosis in a bitch submitted to conventional OH, followed by ovariectomy (OV) due to ovarian remnant syndrome and consequent intraperitoneal adhesions caused by successive surgical interventions. Case: A 11-year-old mixed breed medium size bitch with a history of stump pyometra and ovarian remnant syndrome (SOR) was treated at the Veterinary Hospital-HV of UFPA after 2 previous surgeries. It had been spayed using conventional OH and underwent ovariectomy OV approximately 4 years ago, as it showed signs of estrus after the first surgery, characterizing SOR. On physical examination, its abdomen was distended especially in the left hemiabdomen, with no palpable pain. Ultrasonography showed a cavity in the topographic area of the left kidney, with anechoic content, thin walls, and defined contour. There were nonvascularized tubular structures, suggesting hydroureter and severe hydronephrosis. Exploratory celiotomy was performed, showing the intense presence of abdominal adhesions, followed by an incision in the abdominal midline from the xiphoid process in a caudal direction to the pubis, thereby showing the left kidney. After vesical drainage of 900 mL of renal filtrate, atrophy of the renal parenchyma and preservation of the renal capsule was considered, resulting in its complete resection, followed by the synthesis of the abdominal wall. In the postoperative period, the patient was properly monitored and obtained a satisfactory outcome manifested by a complete recovery. After vesical drainage of 900 mL of renal filtrate, atrophy of the renal parenchyma and preservation of the renal capsule only was considered, resulting in its complete resection, followed by the synthesis of the abdominal wall. In the postoperative period, the patient was properly monitored and obtained a satisfactory outcome manifested by a complete recovery. After vesical drainage of 900 mL of renal filtrate, renal parenchymal atrophy and preservation of the renal capsule only was adopted. Discussion: The choice of the conventional OH technique, followed by the failure to perform, favored the formation of adhesions only diagnosed late. Less invasive alternatives achieved less long-term damage. Excessive intracavitary manipulation and reaction to the nylon suture thread favored the development of these adhesions, and consequently, unilateral obstruction of the left ureter, hydroureter, hypertrophy, and destruction of the renal parenchyma, led the patient to undergo a third surgery, namely, unilateral nephrectomy. In this case, no changes were observed in serum levels, leaving only a subtle abdominal enlargement with hydronephrosis installed silently. There was no possibility of carrying out initial surgical planning, as the affected kidney, making unilateral nephrectomy necessary. Currently, the patient has normal renal function in the contralateral organ, with no clinical or laboratory changes because the affected kidney was not functional, making unilateral nephrectomy necessary. Currently, the patient has normal renal function with no clinical or laboratory changes because the affected kidney was not functional, making unilateral nephrectomy necessary. Currently, the patient has normal renal function in the contralateral organ, with no clinical or laboratory changes. Keywords: ovariohystectomy, ovariectomy, adherence, hydronephrosis, bitch.